2018
DOI: 10.1002/jcb.27672
|View full text |Cite
|
Sign up to set email alerts
|

The effects of fatty acids consumption on OPG/RANKL/RANK system in cardiovascular diseases: Current status and future perspectives for the impact of diet‐gene interaction

Abstract: Cardiovascular disease (CVD) is an overall term that comprises a number of related pathologies, these include peripheral arterial disease, cerebrovascular disease, coronary heart disease (CHD), venous thromboembolism, and rheumatic and congenital heart diseases. Fatty acids in the diet have been reported to affect CVD. The OPG/RANKL/RANK system appears to have a role in CVD outcomes. However, there have been few studies on the impact of dietgene interaction for effects of fatty acids consumption on the OPG/RAN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…In addition to RANKL and TRAIL, OPG could bind to some other agents like glycosaminoglycans (GAGs), von Willebrand Factor, Factor VIII-von Willebrand Factor complex, and syndecan-1 [72]. The RANKL/RANK/OPG system has important roles in various organs and conditions such as bone modeling and remodeling [61], cancer cells [73], pregnancy [63] , immune system [74], and cardiovascular disease [75].…”
Section: Rankl/rank/opg Pathwaymentioning
confidence: 99%
“…In addition to RANKL and TRAIL, OPG could bind to some other agents like glycosaminoglycans (GAGs), von Willebrand Factor, Factor VIII-von Willebrand Factor complex, and syndecan-1 [72]. The RANKL/RANK/OPG system has important roles in various organs and conditions such as bone modeling and remodeling [61], cancer cells [73], pregnancy [63] , immune system [74], and cardiovascular disease [75].…”
Section: Rankl/rank/opg Pathwaymentioning
confidence: 99%
“…OPG is a member of the tumor necrosis factor receptor superfamily and is widely expressed in a variety of tissues (9). Recent studies have reported that OPG is functional only in the bone, and osteoblasts regulate the differentiation of osteoclasts via the secretion and expression of OPG and RANKL (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…Osteoprotegerin (OPG) is a cytokine member of the TNF receptor superfamily and binds two ligands, which are receptor activators of nuclear factor κB ligand (RANKL) and TNF-related apoptosis-inducing ligand (TRAIL) (7,8). Further, OPG could inhibit RANKL and RANK binding, reduce osteoclast activity, and impede bone resorption (9). It suggests that the OPG/RANKL/RANK system plays a critical role in maintaining bone balance, and is the physiological basis for regulating osteoclast formation (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Osteoprotegerin (OPG) is a member of the TNF receptor superfamily which bonds to the receptor activators of nuclear factor κB ligand (RANKL) and TNF-related apoptosis-inducing ligand (TRAIL) [ 7 , 8 ]. Furthermore, OPG has been shown to inhibit RANKL and RANK binding, reduce osteoclast activity, and impede bone resorption [ 9 ]. These findings suggest that the OPG/RANKL/RANK system plays a critical role in maintaining bone balance, and represents the physiological basis for regulating osteoclast formation [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%